Gastric ghrelin, GOAT, leptin, and leptinR expression as well as peripheral serotonin are dysregulated in humans with obesity. Issue 6 (19th January 2016) - Ritze, Y.; Schollenberger, A.; Hamze Sinno, M.; Bühler, N.; Böhle, M.; Bárdos, G.; Sauer, H.; Mack, I.; Enck, P.; Zipfel, S.; Meile, T.; Königsrainer, A.; et al.
Abstract: Background: Gastrointestinal hormone release and the regulation of appetite and body weight are thought to be dysbalanced in obesity. However, human data investigating the expression of gastrointestinal hormones in the obese are rare. We studied the expression of ghrelin, leptin, and the serotonergic system in stomach tissue and serum of obese and non‐obese individuals. Methods: Gastric tissue and serum were collected from 29 adult obese (BMI 48.7 ± 10.6 kg/m 2 ; mean ± SD) who underwent laparoscopic sleeve gastrectomy. Gastric biopsies, surgery specimen or serum was obtained from 35 adult non‐obese humans (BMI 22.7 ± 1.9 kg/m 2 ). Ghrelin, ghrelin O‐acyl transferase (GOAT), leptin, leptin receptor, and tryptophan hydroxylase 1 (TPH1) mRNA expression were measured by qRT‐PCR. Serotonin (5HT) and leptin protein concentration were quantified in tissue extracts and serum; GOAT and ghrelin‐positive cells were immunohistologically quantified in tissue. Additionally, 21 blood immune markers were analyzed. Key Results: In gastric tissue, GOAT‐positive cells were reduced ( p < 0.01), but ghrelin‐positive cells and mRNA were increased (both p < 0.05) in obese compared with non‐obese individuals. Gastric leptin ( p < 0.001) and leptin receptor ( p < 0.001) mRNA expression, as well as leptin concentrations in serum ( p < 0.001), were increased in obese compared with non‐obese individuals. Serum 5HT was reduced ( p < 0.05), while tissue 5HT and TPH1 mRNA were reduced only by trend. Interleukin 1 receptor a (IL1Ra), IL‐8, IL‐12, and monocyte chemoattractant protein 1 (IL1Ra) were increased and IL1Ra correlated negatively with serum leptin. Conclusions & Inferences: Our data indicate that obesity causes a dysregulation of gastrointestinal hormones at the tissue level and serum, including a negative correlation with an increased marker of subclinical inflammation. Abstract : Gastrointestinal hormone release and the regulation of appetite and body weight are thought to be dysbalanced in obesity. We asked whether ghrelin, GOAT, leptin, and leptinR expression demonstrates an increased expression in the stomach tissue and blood and also correlates with elevated inflammatory markers in obese compared with non‐obese humans. Our data indicate that obesity causes a dysregulation of gastrointestinal hormones at the tissue level and serum, including a negative correlation with an increased marker of subclinical inflammation.